IMPLEMENTATION VOICE OVER INTERNET PROTOCOL (VOIP) AS A COMMUNICATION MEDIA BETWEEN UNIT AT UNIVERSITY MUHAMMADIYAH METRO - Arif Hidayat; Ismail Puji Saputra (STMIK Pringsewu Lampung, 2018)
VOIP (Voice over Internet Protocol) is the theology that makes the intranet network even the internet to be able to do voice communications remotely directly. Analog voice signals, such as those heard when communicating on the phone is converted into digital data and transmitted over the network in the form of data packets in real time. In VoIP communications, the user makes a phone connection through a terminal in the form of a PC or a regular telephone (smartphone). With telephones using VoIP, many benefits can be taken include: 1) in terms of cost obviously cheaper than traditional phone rates, 2) network-free, if the internet network is broken VOIP can still be used with notes connected to wifi or wired network, 3) maintenance costs can be pressed due to voice and network data apart, so IP Phone added, moved and changed. In this research, VOIP is implemented at UM Metro. UM Metro has 3 campuses (Campus 1, Campus 2 and Campus 3) are different areas of location, but still in one City. The result of Voice Over Internet Protocol (VOIP) as communication media between units at UM Metro shows the result of 85, 7% (Strongly Agree) and 14, 3 (Agree), it can be concluded with the existence of VOIP is very feasible for use as a medium of communication.